2004
DOI: 10.1182/blood-2003-05-1603
|View full text |Cite
|
Sign up to set email alerts
|

Geldanamycin and herbimycin A induce apoptotic killing of B chronic lymphocytic leukemia cells and augment the cells' sensitivity to cytotoxic drugs

Abstract: IntroductionB chronic lymphocytic leukemia (CLL) is characterized by the clonal expansion of CD5 ϩ CD19 ϩ B-lymphoid cells. Although CLL cells proliferate slowly, defective apoptosis results in progressive accumulation of the malignant clone. [1][2][3] The clinical course of CLL is highly variable. Although a proportion of patients survive for extended periods without the need for clinical intervention, others undergo rapid disease progression and require aggressive treatment. Recent studies have established t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 46 publications
5
37
0
1
Order By: Relevance
“…An alternative explanation for the cytotoxicity of Hsp90 inhibition in all CLL samples is that cell death resulted from the loss of survival signals consequent to depletion of Akt, as proposed by Jones DT et al (2004a). Thus, Akt is thought to play a key role in maintaining the viability of CLL cells in vivo independently of any effect on the MDM2-p53 pathway (Jones et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…An alternative explanation for the cytotoxicity of Hsp90 inhibition in all CLL samples is that cell death resulted from the loss of survival signals consequent to depletion of Akt, as proposed by Jones DT et al (2004a). Thus, Akt is thought to play a key role in maintaining the viability of CLL cells in vivo independently of any effect on the MDM2-p53 pathway (Jones et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent study has shown that inhibition of Grp94 expression by geldanamycin in chronic lymphocytic leukaemia cells induces apoptosis with modest cytoprotective effects of primary haematopoietic progenitors from normal bone marrow (Jones et al, 2004). In addition, targeting cancer cells with an antisense or RNAi procedure against Grp94 has shown increased chemosensitivity or radiosensitivity (Reddy et al, 1999;Kubota et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Because these pathways are constitutively activated in many tumor cells, GM is expected to have a potent antitumor activity (Gorre et al, 2002;Minami et al, 2002;Bisht et al, 2003). GM and its less toxic derivative 17-allylamino-17-demethoxygeldanamycin (17-AAG) have been reported to inhibit tumor cell growth by inducing apoptosis and, in certain cell types, differentiation (Mu¨nster et al, 2001;Jones et al, 2004;Mitsiades et al, 2006). GM is reported to enhance tumor cell sensitivity to various cytotoxic agents and ionizing radiation through the inhibition of nuclear factor (NF)-kB activation and its downstream survival signals (Lewis et al, 2000;Broemer et al, 2004).…”
Section: Introductionmentioning
confidence: 99%